A multi-dimensional model of Enterprise Resource Planning critical success factors. Issue 1 (2nd January 2020) - Vargas, Marcela Alejandra; Comuzzi, Marco
ABSTRACT: Recent literature on ERP implementation Critical Success Factors has focused on how different factors characterizing the context of the implementing firm, such size or culture, affect the relative importance of CSFs. Based on a systematic analysis of recent literature, this paper proposes a comprehensive model of contextual factors affecting the importance of ERP implementation CSFs. The proposed model answers the call for research on CSF to focus more on context determining CSF effectiveness. It also helps practitioners to identify important success factors in ERP implementations, calling for more research about specific contextual factors and CSFs in determining ERP implementation success.